RE-READING HATTA'S THINKING IN MOVEMENT: BETWEEN ISLAM AND NATIONALISM - Rian Wahyudin (Mimbar Agama Budaya, 2021)
Abstract. This article reviews the perspectives of Mohammad Hatta as one of the Indonesian founding fathers in regards between Islam and nationalism.  Many scholars, historians, and intellectuals have deemed that Hatta was a secular nationalist who separated national propositions from religious values.  Whereas, on the contrary, both his actions and thoughts were in line with the noble of Islamic values, not only when he wanted to establish the Indonesian Islamic Democratic Party in 1967 with several other activists such as alumni of Islamic Students Association (HMI), PII, the Indonesian Islamic Syarikat Party, and Nahdlatul Ulama (NU) figures, but also Hatta's Islamic integrity already seen during the movement, when he was active in both the Indonesian Association (PI) organization in 1921-1930 and the Indonesian National Education (PNI Baru) in 1931-1932. For instance, Hatta proposed his thoughts on peace, which he took from Qur’an surah al-Fatihah verse two.  According to him, the concept of peace is the highest law in Islam; therefore, every free nation must uphold peace. He continued, the statement "God is the Most Gracious and Most Merciful" must be applied to create security and convenience among human beings. In February 1927, while serving as the administrator of the Indonesian Association in the Netherlands, Hatta and Nazir Pamontjak, Ahmad Subardjo, Gatot Tarumihardja, and Abdul Manaf were serving as the administrator of the Indonesian Association became delegators at the presidium meeting "Congress Against Imperialism and Colonial Oppression."  This event was organized by the “League Against Imperialism and for National Independence” in Brussels, Belgium.  There Hatta and his fellows sat on a par with delegates from other countries such as Chen Kuen and Liau Hansen (China), Roger Baldwin (United States), Jawaharlal Nehru (India), Willi Munzenberg and Georg Ledebour (Germany), and several delegates from France, Belgium, Latin America, England, and Czechoslovakia to oppose all forms of oppression and demand the independence of Indonesia and other occupied countries to achieve world peace.  Moreover, the identity of  Mohammad Hatta is known well as a figure who came from a family of well-known merchants and scholars in Minang, coupled with his expertise in associating with nationalist figures, made Islamic integrity not appeared by attributive religious symbols, but rather by his behavior, thoughts, and attitudes in everyday life. Abstrak. Artikel ini mengulas tentang pemikiran salah satu bapak bangsa, Mohammad Hatta mengenai hubungan antara Islam dan nasonalisme. Banyak Sarjana, Sejarawan dan Cendikiawan masih menganggap bahwa Bung Hatta adalah seorang nasionalis sekuler, memisahkan soal-soal kebangsaan dari ajaran agama. Tindak-tanduk bahkan pemikirannya malah sejurus dengan nilai-nilai luhur Islam, bukan hanya saat dirinya dan beberapa aktivis lain seperti alumni HMI, PII, Partai Syarikat Islam Indonesia dan tokoh NU yang hendak mendirikan Partai Demokrasi Islam Indonesia pada tahun 1967, keberislaman Bung Hatta justru sudah terlihat pada masa pergerakan baik saat aktif di organisasi Perhimpunan Indonesia (PI) tahun 1921-1930 maupun di Pendidikan Nasional Indonesia (PNI Baru) tahun 1931-1932. Pemikirannya tentang perdamaian misalnya Hatta justru mengambilnya dari Surat al-Fatihah ayat dua. Konsep damai menurutnya hukum yang paling tinggi dalam Islam, oleh karenanya tiap-tiap bangsa yang merdeka harus menjunjung tinggi perdamaian. Menurutnya, “Allah yang Maha Pengasih dan Maha Penyanyang” itu harus diamalkan agar tercipta keamanan dan kenyamanan antar sesama umat manusia. Pada bulan Februari 1927 saat menjadi pengurus Perhimpunan Indonesia di Belanda, Bung Hatta bersama Nazir Pamontjak, Ahmad Subardjo, Gatot Tarumihardja dan Abdul Manaf menjadi delegator pada rapat presidium “Kongres Menentang Imperialisme dan Penindasan Kolonial”. Kegiatan ini diselenggarakan oleh “Liga Menentang Imperialisme dan untuk Kemerdekaan nasional” di Brussel, Belgia. Di sana Hatta dan kawan-kawan duduk sejajar dengan delegator dari negara lain seperti Chen Kuen dan Liau Hansin, (China), Roger Baldwin (Amerika Serikat), Jawaharlal Nehru (India), Willi Munzenberg dan Georg Ledebour (Jerman), dan beberapa utusan lain dari Prancis, Belgia, Amerika Latin, Inggris dan Cekoslovakia untuk menentang segala bentuk penindasan dan menuntut kemerdekaan negara Indonesia dan negara lainnya yang sedang dijajah agar terwujudnya perdamaian dunia. Jati diri Bung Hatta yang berasal dari keluarga saudagar dan ulama masyhur di Ranah Minang ditambah dengan kepiawaiannya dalam bergaul dengan tokoh-tokoh nasionalis membuat corak keberislaman Hatta tidak ditonjolkan dengan simbol-simbol agama yang atributif, melainkan ditonjolkan dengan tingkah laku, pemikiran dan sikap dalam kehidupan sehari-hari.